2017
DOI: 10.1038/s41598-017-07026-w
|View full text |Cite
|
Sign up to set email alerts
|

Controlling bi-anisotropy in infrared metamaterials using three-dimensional split-ring-resonators for purely magnetic resonance

Abstract: We propose and demonstrate the strategy to control bi-anisotropic response in three-dimensional split-ring-resonators (3D-SRRs) array for purely magnetic resonance in the mid-infrared region. By using a metal-stress-driven self-folding method, inversion symmetry along a propagation axis of 3D-SRRs was controlled. The inversion symmetry of 3D-SRRs realized non-bi-anisotropic response of a magnetic resonant mode at around 10 μm in wavelength resulting in purely magnetic resonance with high transmission of 70%. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…For experimental realization of the 3D-SRRs, metal-stress-driven self-folding method 17 , 18 , 24 , 25 as shown in Fig. 1(a) was employed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For experimental realization of the 3D-SRRs, metal-stress-driven self-folding method 17 , 18 , 24 , 25 as shown in Fig. 1(a) was employed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, planar structures, which are frequently used in metamaterial studies, have, in principle, no bi-anisotropy although there is a small amount of bi-anisotropy due to the presence of the substrate that breaks the inversion symmetry. On the other hand, three-dimensional (3D) structures have a great potential to achieve and control the bi-anisotropic response in metamaterials 10 18 . So far, we have demonstrated that 3D split ring resonators (SRRs) show bi-anisotropic response at magnetic resonance and controllability of this bi-anisotropic response through inversion symmetry 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before deposition of gold, buffered hydro fluid treatment was performed to get better adhesion between silicon and gold. After forming the structures on the silicon substrate, inductive coupled plasma reactive ion etching (ICP-RIE, SAMCO, RIE200iPT) was performed with parameters of CF 4 plasma of flow rate of 20 sccm, pressure of 0.15 Pa, ICP power of 500 W, and forward power of 0 W. By setting forward power to 0 W, only the silicon substrate was isotropically etched [11,12]. Transmission spectra measured by the Fourier transform infrared (FT-IR) spectrometer (JASCO system FT/IR-6300FV) are shown in Fig.…”
Section: Preventing Red Shift Due To Substratementioning
confidence: 99%
“…While a planar SRR (PSRR) can be fabricated using conventional lithography, fabrication of a vertical SRR (VSRR) is challenging, often requiring the combination of lithography and plating [10,18,30], deposition, or metal-stress driven self-folding [31]. However, these techniques require that the SRRs be bound to the top surface of the substrate, preventing any vertical displacement.…”
Section: Introductionmentioning
confidence: 99%